Perancangan UI UX Desigen Aplikasi Peminjaman Buku Perpustakaan Berbasis Mobile Pada SMA Negeri 31 Jakarta - Qausar, Aidil (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2022)
The transition to technological progress is currently so fast, the library of SMA Negeri 31 Jakarta has such great user enthusiasm, by having a series of books that vary and of course comply with library standards. To be able to borrow books for a relatively long time, students are required to become members of the school library. The flow of student book borrowing and students choose the type of book they want, then the book is handed over to the librarian to be recorded in the library's main book. When returning a book, students submit the book to the librarian and the officer validates or checks the data on the borrowing date and the date of returning the book. Problems experienced by students such as searching in advance for the category of books they want to borrow, students submitting library membership cards to be filled in with administrative data for borrowing or returning books which are still done manually. Students and students must remember the difference between the borrowing date and the return date, if it exceeds the loan time limit, the student will get a fine due to delays in returning books. Experience) Design of library book lending. This discussion focuses on several things, starting from UI UX design. User friendly application design using the waterfall and UCD methods. Development of features that are in accordance with needs, carrying out prototypes or simulations directly to students at SMA Negeri 31 Jakarta. With the hope that users can better understand and adapt easily to applications that are made to maximize students and students in borrowing library books. And is expected to produce applications with a more modern design, user friendly and responsive when used